2021
DOI: 10.3389/fchem.2021.743060
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Complexity of e-Cigarette Aerosols Compared With the Smoke From a Tobacco Burning Cigarette

Abstract: Background: As e-cigarette popularity has increased, there is growing evidence to suggest that while they are highly likely to be considerably less harmful than cigarettes, their use is not free of risk to the user. There is therefore an ongoing need to characterise the chemical composition of e-cigarette aerosols, as a starting point in characterising risks associated with their use. This study examined the chemical complexity of aerosols generated by an e-cigarette containing one unflavored and three flavore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…In our study, only acetaldehyde increased with the higher nicotine product (BB57); however, its concentration (0.10 µg puff -1 ) was still 160 times lower than the maximum level proposed by AFNOR (16 µg puff -1 ) 91 . A comparison of the emissions of an e-liquid with similar PG/VG ratio (1:1) emitted by a relatively similar Vype device (ePen) that uses a silica wick showed that formaldehyde at a concentration of 0.59 µg puff -1 was 8× higher and acetaldehyde at a concentration of 0.18 µg puff -1 was 2× higher than in the emissions presented herein (Table 3) 92 . In both studies, the values were below the maximum level proposed by AFNOR 91 .…”
Section: Polycyclic Aromatic Compoundsmentioning
confidence: 45%
“…In our study, only acetaldehyde increased with the higher nicotine product (BB57); however, its concentration (0.10 µg puff -1 ) was still 160 times lower than the maximum level proposed by AFNOR (16 µg puff -1 ) 91 . A comparison of the emissions of an e-liquid with similar PG/VG ratio (1:1) emitted by a relatively similar Vype device (ePen) that uses a silica wick showed that formaldehyde at a concentration of 0.59 µg puff -1 was 8× higher and acetaldehyde at a concentration of 0.18 µg puff -1 was 2× higher than in the emissions presented herein (Table 3) 92 . In both studies, the values were below the maximum level proposed by AFNOR 91 .…”
Section: Polycyclic Aromatic Compoundsmentioning
confidence: 45%
“…It can be suggested that falvoring chemicals and nicotine play an important role in the production of ROS [39][40][41], and the amount and proportions vary from product to product [42]. Nevertheless, the studies also showed that the levels of free radicals are lower in e-fluid and the gas phase of aerosol and heat-not-burn products compared to traditional cigarettes, and contain fewer toxic substances at lower concentrations [43]. An exposure of tissues to free radicals can result in damage to the proliferation, survival and inflammation pathways in cells [36].…”
Section: Chemical Components and Toxins Of E-cigarette Aerosolmentioning
confidence: 99%
“…As a result of no high-temperature combustion phenomenon, the heating temperatures of electronic cigarettes are much lower than those of the burning cigarettes. The electronic cigarettes could reduce the complexities and concentrations of harmful chemicals in aerosols compared with the traditional cigarettes . It substantially reduces smokers’ exposures to the toxic substances. , The effects of harm reduction brought by electronic cigarettes are effective. The success rates of smoking cessation through the use of electronic cigarettes are nearly twice that of nicotine replacement therapy, such as nicotine patches and nicotine gum .…”
Section: Introductionmentioning
confidence: 99%
“…The electronic cigarettes could reduce the complexities and concentrations of harmful chemicals in aerosols compared with the traditional cigarettes. 1 It substantially reduces smokers' exposures to the toxic substances. 2,3 The effects of harm reduction brought by electronic cigarettes are effective.…”
Section: Introductionmentioning
confidence: 99%